Soil microbiology, ecology, and biochemistry - Paul, Eldor Alvin; Paulman, Paul M. , 1953- (Academic Press, 2007)
This is a comprehensive text for the study of soil ecology. It covers the subject in sufficient depth for an advanced undergraduate or post graduate course in soil microbiology and biochemistry...the reader soon begins to relate the discussions to plant health and fruit development. The topics are covered to a depth that addresses a wide range of readers, from those who wish an overview of the subject to those who need to know the fundamental microbiology or biochemistry. The 18 chapters are divided into five broad subject areas, starting with background and continuing through the soil biota, interactions, biochemistry, and concluding with the impact of human processes. There is little current appreciation of the impact of cultivation on soil ecosystems, thus we employ few strategies to manage these systems to our advantage. A book like this is food for though." - Gary Strachan, in FRUIT GROWER